Collimation of the kiloparsec-scale radio jets in NGC 2663. Issue 2 (12th September 2022) - Velović, Velibor; Filipović, M D; Barnes, L; Norris, R P; Tremblay, C D; Heald, G; Rudnick, L; Shabala, S S; Pannuti, T G; Andernach, H; Titov, O; Waddell, S G H; et al.
ABSTRACT: We present the discovery of highly collimated radio jets spanning a total of 355 kpc around the nearby elliptical galaxy NGC 2663, and the possible first detection of recollimation on kiloparsec scales. The small distance to the galaxy (∼28.5 Mpc) allows us to resolve portions of the jets to examine their structure. We combine multiwavelength data: radio observations by the Murchison Widefield Array (MWA), the Australian Square Kilometre Array Pathfinder (ASKAP) and the Australia Telescope Compact Array (ATCA), and X-ray data from Chandra, Swift, and SRG/eROSITA. We present intensity, rotation measure, polarization, spectral index, and X-ray environment maps. Regions of the southern jet show simultaneous narrowing and brightening, which can be interpreted as a signature of the recollimation of the jet by external, environmental pressure, though it is also consistent with intermittent active galactic nuclei or complex internal jet structure. X-ray data suggest that the environment is extremely poor; if the jet is indeed recollimating, the large recollimation scale (40 kpc) is consistent with a slow jet in a low-density environment.